Peacemakers in Israel-Palestine : dialogues for a just peace - Hostetter, Robert, 1946- (Abingdon, Oxon ; New York, NY : Routledge, 2022)
"This book offers an analysis of the major sources of the Israeli-Palestinian conflict and suggests principles and processes for building a peacemaking platform. The primary aim of this book is to analyze the crucial roles and capacities of mid-level, nongovernmental peacemakers as they provide unique approaches to transforming the Israel-Palestinian conflict. It also aims to analyze and experience dialogue as the primary mode of peacemaking communication. The two-part format of this book creates a structural dialogue. Part One provides an academic introduction to the Israeli-Palestinian conflict, why it matters, the role of identities, and strategies for transforming the conflict based on international law and human rights. Part Two is presented in a dialogue format, providing further conflict analysis through storytelling and dialogues with peacemakers. This book will be of great interest to anyone engaged with peace and conflict transformation, ethnography, social justice, communication studies, and Middle Eastern studies, human rights and international law"--
Orientations : an introduction -- Coming to terms -- A conflict of identities -- Peacemaker identities -- Dialogues for a just peace -- A platform for a just peace -- Abdelfattah Abusrour, "the arts as beautiful resistance" -- Ghassan Andoni, "the lessons of engagement" -- Arik Ascherman, "Jewish tradition and human rights" -- Hanan Ashrawi, "peacebuilding and nation building" -- Naim Ateek, "a journey for justice and peace" -- Uri Avnery, "changing public opinion in Israel" -- Sami Awad, "the power of nonviolence" -- Sam Bahour, "the business of peacemaking" -- Eitan Bronstein, "what reconciliation requires" -- Emad Burnat, "5 broken cameras: a film for peace" -- Elias Chacour, "get up, move ahead, make peace" -- Mona El-Farra, "a comprehensive solution" -- Jeff Halper, "struggles for a just peace" -- Jonathan Kuttab, "universal principles, international law" -- Gideon Levy, "telling the whole truth" -- Jessica Montell, "a mandate for human rights" -- Ilan Pappe, "the only nonviolent alternative" -- Mitri Raheb, "the infrastructure of hope" -- Estephan Salemeh, "work for the common good" -- Yonatan Shapira, "three sails for Gaza" -- Gila Svirsky, "a better world for all of us."
Includes bibliographical references and index.
Keywords: Arab-Israeli conflict -- 1993- -- Peace; Arab-Israeli conflict -- Peace; Jewish-Arab relations; Peace-building -- Israel; Peace-building -- Palestine; Political activists -- Israel -- Interviews; Political activists -- Palestine -- Interviews